Psychological and pedagogical aspects of students professional creativity development (Pedagogy of Higher and Secondary Education, 2012)
Chuvasova N. O. Psychological and pedagogical aspects of students professional creativity development.In the article a theoretical survey and analysis of scientific literature about professional creativity developing in up-to-date psychology, psychological and pedagogical fundamentals of students’ thinking are discussed and characterized in the article.
Keywords: профессиональное мышление; техническое творчество; решение учебных задач профессионального направления